Single-cell RNA and transcriptome sequencing profiles identify immune-associated key genes in the development of diabetic kidney disease - Zhang, Xueqin; Chao, Peng; Zhang, Lei; Xu, Lin; Cui, Xinyue; Wang, Shanshan; Wusiman, Miiriban; Jiang, Hong; Lu, Chen (Frontiers in Immunology, 2023)
There is a growing public concern about diabetic nephropathy.It's important to discover immune-associated biomarkers that can be used to predict diabetic nephropathy progression.This study conduct the analysis though five datasets of DKD from gene expression omnibus.We conducted single-cell RNA sequencing analysis by CellMarker and CellPhoneDB on public datasets to identify the specific cell types and cell-cell interaction networks related to DKD.DEGs were identified from four database.The regulatory relationship between DN-related characters and genes was evaluated by using WGCNA analysis.GO and KEGG database were applied to define the enrichment of each term.Subsequently, immune cells infiltration between DKD and the control group were identified, and the connection Matrix between the core genes and immune cells or function were illuminated.Furthermore, RcisTarget and GSEA were conducted on public datasets for the analysis of regulation relationship of key genes and revealed the correlation between 3 key genes and top 20 genetic factors involved in DKD.Finally, the expression of key genes between patients with 35 DKD and 35 controls were examined by ELISA, and assessed the relationship between progression of DKD rate and hub gene plasma levels in a cohort of 35 DKD patients.There were 8 cell types between DKD and control, as well the number of connections between macrophages and other cells was higher than that of other seven cell groups. We identified 356 different expression genes from the RNA-seq, which are enriched in urogenital system development, kidney development, platelet alpha granule and glycosaminoglycan binding pathways.WGCNA was conducted to construct 13 gene modules.Then we overlapped the DEGs, WGCNA and scRNA-seq, SLIT3, PDE1A and CFH were screened as the closely related genes to diabetic nephropathy.Besides, there is a remarkably positive correlation between T cells gamma delta, Macrophages M2, Mast cells resting and the three key genes named SLIT3, PDE1A and CFH, and B cells naive, Neutrophils were negatively correlated with the three key genes in the results of immune infiltration.Besides, hsa-miR-4739 and hsamiR-320c play significant roles in the regulation of the key genes.Comparatively to controls, DKD patients showed high levels of SLIT3,PDE1A, and CFH.Higher levels of SLIT3,PDE1A, and CFH are associated with a lower end point.